Cardiac Arrest in Labour Leading to Perimortem Caesarean Section in a Woman with a Body Mass Index >46 with a Successful Outcome - Saadia Farrakh; Charles Bircher; Haroona Khalil (European Medical Journal, 2016)
A 42-year-old primigravida was admitted to the delivery suite for induction of labour at term due to gestational diabetes and pre-eclampsia. Her booking body mass index was 46 and she had known, well-controlled asthma. Active labour was established. When she was 8-9 cm dilated, she required fetal blood sampling. At the end of the procedure, the patient had a sudden cardiac arrest. High-flow oxygen at the rate of 15 litres was started with bag and mask and immediate maternal cardiopulmonary resuscitation (CPR) was commenced. After 3 minutes of CPR, a decision was made to perform a perimortem caesarean section to aid effective resuscitation. The baby was delivered swiftly. The patient began to respond and showed signs of life. The patient was transferred to theatre for suturing. The massive postpartum haemorrhage protocol was initiated. The patient was transfused with three units of packed red blood cells, three units of fresh frozen plasma, and two units of platelets. The total blood loss was about 3.5 litres. She recovered in an intensive therapy unit. After 72 hours, her clinical assessment excluded any neurological or other ongoing morbidity. Amniotic fluid embolism was suspected as the cause for cardiac arrest. As the patient made a very quick postoperative recovery, a bronchial lavage was thought to be clinically unnecessary. The baby, initially admitted to the baby unit, was also discharged on Day 3 of life with no morbidity. Both mother and baby were completely well at a 3-month postnatal follow-up visit.